RTHP-09. DYSREGULATION OF Wnt SIGNALING PATHWAY CORRELATES WITH TREATMENT OUTCOME IN GLIOBLASTOMA MULTIFORME. (5th November 2018) - Weterings, Eric; Morrison, Christopher; Gravbrot, Nicholas; Hammer, Michael; Mahadevan, Daruka; Stea, Baldassarre
Abstract: Glioblastoma multiforme (GBM) is the most common and most aggressive primary brain cancer with a median life expectancy of 13–15 months after surgery and chemo-radiation treatment. GBM is hallmarked by a poor response to radiation therapy (RT), which is generally attributed to upregulation of several DNA repair pathways. To identify pathways which predict poor chemo-radiation treatment outcome, we conducted a retrospective clinical-genetic study in which we evaluated the mRNA expression profiles of 24 GBM tumor samples, stratified on the basis of patient survival post chemo-radiation treatment. All patients were treated at our institution by surgical resection and intensity-modulated RT with concurrent and adjuvant temozolomide. Expression profiles were obtained utilizing a commercially available PanCancer Pathways Panel (NanoString Technologies, Inc.). Our data analysis shows a distinctly significant correlation between 5 members of the Wnt pathway and overall patient survival. A 2- to 9-fold higher expression of negative regulators of the Wnt pathway and a 2- to 3-fold lower expression of positive Wnt regulators was observed in tumor material of patients with a longer than median survival. We conclude that upregulation of the Wnt pathway correlates with poor chemo-radiation treatment outcome in GBM. In vitro experimentation by other groups has recently demonstrated a role for Wnt signaling in activation of Non-Homologous End-Joining mediated DNA double-strand break repair and the subsequent onset of radio-resistance. These preliminary findings support the hypothesis that the Wnt pathway may be used as a predictive marker for RT outcome in GBM and suggest new strategies to increase the radiation sensitivity of GBM.